1997
DOI: 10.1037/1196-1961.51.2.176
|View full text |Cite
|
Sign up to set email alerts
|

A lateralized comparison of handedness and object proximity.

Abstract: This study was motivated by the emerging hypothesis that right-handers are more strongly lateralized and perform better on various aspects of functional asymmetry than do left-handers. Right-and left-handers •were observed for hand selection responses to a unimanual task of reaching for a small cube in positions of right-and left hemispace, prompting hemispheric decision-making related to hand dominance and attentional (visuospatial) stimuli. As predicted, left-handers did not respond with their preferred limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 27 publications
6
36
2
2
Order By: Relevance
“…Regardless of the affected side, these participants tended to use their dominant righthands to reach for a target in the right field of the workspace and up to a target position of −10° past the body midline (0°) in the contralateral hemispace. This arm selection pattern is similar to the findings of previous studies of healthy adults, in that arm selection changed to the non-dominant left hand at a target position of −10° in the contralateral hemispace of the workspace 7,9,20) . Thus, Pattern A can be called as a "normal-like" arm selection.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Regardless of the affected side, these participants tended to use their dominant righthands to reach for a target in the right field of the workspace and up to a target position of −10° past the body midline (0°) in the contralateral hemispace. This arm selection pattern is similar to the findings of previous studies of healthy adults, in that arm selection changed to the non-dominant left hand at a target position of −10° in the contralateral hemispace of the workspace 7,9,20) . Thus, Pattern A can be called as a "normal-like" arm selection.…”
Section: Discussionsupporting
confidence: 77%
“…A setting used to investigate the issue of limb selection is one in which a patient has to reach an object placed on a wide-ranging workspace [7][8][9][10][11] . Gabbard and colleagues explored this issue, and found that generally a limb transition from the dominant arm to the non-dominant arm among right-handers occurred around 20° past the body midline in the contralateral hemispace 7,9) . Similar findings were found for children and left-handers 8,12) .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, hemispheric bias means that using the ipsilateral hand for reaching can limit biomechanical constraint effects bearing on the movement. In other words, using the contralateral hand for doing such actions requires longer trajectory and body midline crossing, which leads to action efficiency reduction (Gabbard et al, 1997). Recently, some studies suggest other various factors that affect limb selection.…”
Section: Introductionmentioning
confidence: 99%
“…They use their preferred hand in reaching to most objects in their peripheral environment. Therefore, it was concluded that repetition and frequency of reaching with the preferred hand occurs much more frequently than reaching with the non-preferred hand (Gabbard et al, 2003;Gabbard et al, 1997;Pryde et al, 2000;Doyen et al, 2008). According to the kinesthetic perspective, performing actions on each side of body with the ipsilateral hand is defined as hemispheric bias or kinesthetic proficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation